POSITION AND AUTHORITY OF THE PROFESSIONAL DISCIPLINARY COUNCIL IN RESOLVING HEALTH WORKER CASES UNDER LAW NUMBER 17 OF 2023 ON HEALTH - Emma Choerunnisa; Prasetyo Edi (Siber Nusantara Research, 2026)
Abstract: Law Number 17 of 2023 on Health fundamentally reshapes the legal architecture for enforcing professional discipline among Indonesian health workers by establishing the Professional Disciplinary Council (Majelis Disiplin Profesi/MDP), replacing sectoral bodies such as the Indonesian Medical Disciplinary Honor Council (MKDKI). This article analyzes the position, legal basis, and authority of the MDP in handling alleged professional discipline violations by health workers, including its relationship with criminal and civil liability processes. A normative legal method is applied through statutory and conceptual approaches, drawing on Law Number 17 of 2023, Government Regulation Number 28 of 2024, Minister of Health Regulation Number 3 of 2025, and Minister of Health Decree Number HK.01.07/MENKES/775/2025 as primary legal materials. The findings indicate that the MDP holds substantially broader authority than the former MKDKI, since it not only imposes administrative disciplinary sanctions but also issues recommendations that function as a precondition for criminal and civil proceedings against medical and health personnel under Article 308 of the Health Law. This mechanism operates as a primum remedy intended to prevent the criminalization of health workers for inherent medical risks, yet it simultaneously raises concerns regarding the certainty of examination timeframes, potential overlap with the investigative function of law enforcement, and the dependence of civil proceedings on the initiative of the health worker being sued. The article recommends strengthening technical regulations on examination deadlines, clarifying the boundary between disciplinary and investigative authority, and improving health workers' awareness of their rights and procedures before the MDP to achieve legal certainty, utility, and justice for both health workers and patients.